2022
DOI: 10.1097/tp.0000000000004087
|View full text |Cite
|
Sign up to set email alerts
|

Casirivimab–imdevimab to Prevent SARS-CoV-2 Infections in Solid Organ Transplant Recipients

Abstract: neutralizing mAbs with activity against a variety of virus variants, such as Omicron.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…Preexposure prophylaxis with casirivimab-imdevimab was not authorized under EUA in the United States, but in France was authorized by the National French Health Authority. 51 , 52 In this context, Dimeglio et al 51 reported on 182 SOT recipients who had low or undetectable antibody responses to vaccines, and who received 2 doses of casirivimab/imdevimab 1 mo apart as preexposure prophylaxis during the Delta variant surge. This was highly successful, as no patient who received this preexposure prophylaxis developed COVID-19, whereas 13 of 296 (4.4%) of those who did not receive casirivimab/imdevimab developed COVID, of whom 3 had severe disease and 1 died.…”
Section: Monoclonal Antibodies For Prophylaxismentioning
confidence: 99%
See 1 more Smart Citation
“…Preexposure prophylaxis with casirivimab-imdevimab was not authorized under EUA in the United States, but in France was authorized by the National French Health Authority. 51 , 52 In this context, Dimeglio et al 51 reported on 182 SOT recipients who had low or undetectable antibody responses to vaccines, and who received 2 doses of casirivimab/imdevimab 1 mo apart as preexposure prophylaxis during the Delta variant surge. This was highly successful, as no patient who received this preexposure prophylaxis developed COVID-19, whereas 13 of 296 (4.4%) of those who did not receive casirivimab/imdevimab developed COVID, of whom 3 had severe disease and 1 died.…”
Section: Monoclonal Antibodies For Prophylaxismentioning
confidence: 99%
“…This was highly successful, as no patient who received this preexposure prophylaxis developed COVID-19, whereas 13 of 296 (4.4%) of those who did not receive casirivimab/imdevimab developed COVID, of whom 3 had severe disease and 1 died. 51 More recently, Kamar et al 52 reported 1 patient (out of 436 who had received casirivimab/imdevimab for preexposure prophylaxis) who had breakthrough infection with the Omicron variant despite high levels of anti-S antibody. Again, it appears that this use of casirivimab/imdevimab was highly effective during the Delta surge, which speaks to the utility of preexposure prophylaxis as a concept in vulnerable patients.…”
Section: Monoclonal Antibodies For Prophylaxismentioning
confidence: 99%
“…While in Switzerland mAbs are used only as an early treatment, neutralizing anti–SARS-CoV-2 mAbs such as casirivimab/imdevimab were used as pre-exposure prophylaxis in SOT recipients with weak or no humoral response after vaccination (3 doses of an mRNA vaccine). This latter strategy was shown to be efficient in preventing COVID-19 incidence in SOT, compared to untreated controls ( 17 ).…”
Section: Discussionmentioning
confidence: 99%
“…The administration of early treatment with mAbs (casirivimab/imdevimab and sotrovimab) targeting the spike protein of SARS-CoV-2 has been used for high-risk patients with mild to moderate COVID-19, with promising results by reducing morbidity and mortality (13,14). However, data on the efficacy of mAbs in the KTR population remain scarce, especially regarding sotrovimab (14)(15)(16)(17). Some case-control studies performed in KTR showed that the administration of mAbs halted the progression of COVID-19 symptoms and decreased the number of hospitalizations related to COVID-19, with a good safety profile (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation